Ed Ricketts in Army Uniform - Ed Ricketts, Jr.:::Creator::::::::::::
Ed 'Doc' Ricketts standing in uniform while working a little more than a year in the Medical Corps as a clerk. The photo was taken outside Fred & Frances' house.